Indigenous and faith healing for mental disorders : an exploratory study of healers in Accra, Ghana - Kpobi, Lily Naa Ayorkor (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.